Simulation study on hydrogen concentration distribution in hydrogen blended natural gas transportation pipeline. - Weiqing Xu; Yongwei An; Shuangjie Yan; Rui Li; Maolin Cai; Guanwei Jia (PLoS ONE)
Hydrogen is a clean energy source, and blending it with natural gas in existing pipeline networks is a key transition solution for transportation cost reduction. However, during the transportation process, a non-uniform distribution of hydrogen concentration occurs in the pipeline due to gravity. Therefore, it is necessary to study the hydrogen concentration distribution law of hydrogen-blended natural gas in pipelines. The undulation and ball valve pipelines, which are common in transport pipelines, were constructed in this study. The effects of the undulation angle, height, pipeline diameter, ball valve opening, and temperature on the distribution of the hydrogen concentration were investigated using computational fluid dynamic (CFD) methods. The results indicated that the hydrogen concentration gradient changed gently with the larger diameter of the undulating pipeline, minimizing hydrogen accumulation. Higher undulation angle and smaller height differences reduces the hydrogen accumulation risk. Increasing vertical height difference of the pipeline from 5 m to 15 m increased the hydrogen volume fraction gradient by1.3 times. In the ball valve pipeline, the velocity fluctuation decreased as the ball valve opening increased. However, the hydrogen accumulation phenomenon was obvious. The opening increased from 25% to 100% and the hydrogen volume fraction gradient increased more than two times. Selecting delivery conditions with low hydrogen blending ratios, high temperatures, low pressures, and high flow rates reduces the occurrence of hydrogen buildup in the pipeline.